(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: This article’s purpose was to evaluate the results of tonsillectomy–adenoidectomy with Peak PlasmaBlade TnA. Subject and Method: The prospective descriptive study in 67 patients was tonsillectomy – adenoidectomy with Peak PlasmaBlade TnA. Result: The average operating time was 22,60 ± 2,70 minutes. The estimated average blood loss during surgery was 4,40 ± 1,40 ml. The length of hospital stay was 2,37 ± 0,50 days. No post-op bleeding. Conclusion: The method for tonsillectomy – adenoidectomy with Peak PlasmaBlade TnA has many advantages, such as reducing intraoperative blood loss, short surgery time, limited postoperative bleeding and safeness.